Perancangan Sistem Informasi Pelaporan Analisis 10 Besar Penyakit Rawat Jalan di RSUD Bandung Kiwari - Supriadi, Redi; Abdussalaam, Falaah; Sari, Irda (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This research will present the design of an information system for the top 10 outpatient diseases at the Bandung Kiwari Regional General Hospital using Microsoft Visual Studio 2010 software. The development method used is the waterfall method using system modelling in the form of context diagrams, Data Flow Diagrams (DFD), and database design tools in the form of Entity Relationship Diagrams (ERD). Data collection was carried out by means of interviews, observations and literature studies related to the information system design that the researcher created. The aim of this research is to make it easier for officers to process reporting analysis of the top 10 outpatient diseases in an effective and efficient manner. The results of this research show that the use of technology based medical records can be a revolution in opening up a wider range of information, to present various information regarding patient medical record reports that management needs for decision making.